Photography for architects : effective use of images in your architectural practice - Knight, Martine Hamilton (New York, NY : Routledge, 2024)
"Today, online, there is too much visual noise. We live in a world driven by images, but is anyone really looking at them? How does an architect ensure their portfolio is in view of the right audience? Photographs are still as vital to architectural practice as they ever were. Creation and circulation, once in the hands of skilled professionals, is now perceived as being 'free' and within easy reach of all. But where is the clarity? What is the message? By setting up the case for curated image making, decisions around photography can be placed at the centre of architectural practice. Photography for Architects guides the reader through topics such as establishing a visual brand, sharing images online and understanding when to create content in-house and how to commission professionals together with the value that their creative service brings. It explores making books and exhibitions for legacy value, compiling award entries and engaging with trade press. Little understood aspects regarding legal rights and obligations, ethics, copyright and licensing for image use are discussed in clear language, with multiple photographic examples illustrating the various themes throughout. Written by an architectural photographer with over thirty years' experience in commercial practice, this easy-to-read, richly illustrated guide is essential reading for architects and designers alike who are working with images and image makers"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Architectural photography; Architecture and photography